2001
DOI: 10.1097/00001756-200112040-00013
|View full text |Cite
|
Sign up to set email alerts
|

Is perceptual anticipation a motor simulation? A PET study

Abstract: A large body of psychophysical evidence suggests that perception of human movement is constrained by the observer's motor competence. PET measurements of regional cerebral blood flow were performed in eight healthy subjects who were requested, in a forced-choice paradigm, to anticipate the outcome of a single moving dot trajectory depicting the beginning of either mechanical, pointing, or writing movements. Selective activation of the left premotor cortex and of the right intraparietal sulcus was associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 19 publications
3
31
0
2
Order By: Relevance
“…2 Such resonance is probably neurologically hard-wired, as developmental research suggests, but it is most likely a distributed neural mechanism. Moreover, this resonance phenomenon is consistent with the notion of "shared representations", which postulates that perception and action share common cognitive and neural codes [8,12,42,50,54]. According to this model, perception of a given behavior in another 2 The concept of resonance requires both parallel processing, a radically modern idea in Gibson's time, and a group of mechanisms with which to resonate.…”
Section: Introductionsupporting
confidence: 77%
See 2 more Smart Citations
“…2 Such resonance is probably neurologically hard-wired, as developmental research suggests, but it is most likely a distributed neural mechanism. Moreover, this resonance phenomenon is consistent with the notion of "shared representations", which postulates that perception and action share common cognitive and neural codes [8,12,42,50,54]. According to this model, perception of a given behavior in another 2 The concept of resonance requires both parallel processing, a radically modern idea in Gibson's time, and a group of mechanisms with which to resonate.…”
Section: Introductionsupporting
confidence: 77%
“…Such a model is similar to the so-called simulation theory [46]. 3 Evidence for this model derives from neurophysiological investigations [27,28], as well as from several functional imaging studies that have shown similar patterns of neurodynamic activity in the premotor and in the posterior parietal cortices when subjects observe actions performed by another individual and when they actually perform or mentally simulate the same actions [11][12][13]21,22,40,41,75]. One other neuroimaging study [10] has even demonstrated somatosensory activation in a somatotopic manner in the premotor cortex during action observation.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…All activations are summarized in a common schema in the lowest panel on the left side and are also plotted on brain sections on the right side. Activations were taken from the following studies: Execution of action/biological motion, Anderson et al, 1994;Binkofski 1999;Corfield et al, 1999;De Jong, 1999;Ehrsson et al, 2000Ehrsson et al, , 2001Ehrsson et al, , 2002Fox et al, 2001;Hamzei et al, 2002;Haslinger et al, 2002;Kawashima, 1996Kawashima, , 1998Kertzman et al, 1997;Kuhtz-Buschbeck et al, 2001;Lafleur et al, 2002;O'Driscoll et al, 1995;Sadato et al, 1996 Imagery of action/biological motion, Bonda et al, 1995;Decety, 1994;Gerardin et al, 2000;Johnson et al, 2002;Lafleur et al, 2002;Parsons et al, 1995;Shergill et al, 2001;Thobois et al, 2000;Vingerhoets et al, 2002 Observation of action/biological motion, Buccino, 2001;Campbell et al, 2001;Decety, 1997;Iacoboni et al, 1999;MacSweeney, 2000;Manthey et al, 2003;Von Cramon and Schubotz, 2003 Imagery and observation of nonbiological motion and objects, Chaminade et al, 2001;Corbetta et al, 1993;Gerlach et al, 2002;Grabowski et al, 1998;Grafton et al, 1997;Griffiths, 2000a,b;Halp...…”
Section: Dorsal Versus Ventral Pmmentioning
confidence: 99%
“…These tasks overlap in that they require the imagery of a dynamic scene or signal, but differ with respect to the environmental properties that are mentally manipulated or simulated in this way. For instance, the prediction of writing-like trajectories activates dorsalmost PMv, that of pointing-like trajectories the middle PMv (Chaminade et al, 2001), and learning auditory event prediction corresponds to an increase in the inferiormost PMv (Ramnani et al, 2000). Each of these tasks corresponds to sensory events that are usually caused by or engaged in movement of the arm and eyes (spatial locations and orientations), the hand and fingers, sometimes the mouth (object properties), or the vocal effectors (auditory and rhythmic features).…”
Section: S122mentioning
confidence: 99%